A narrative of the captivity of Mrs. Johnson. Containing an account of her sufferings during four years with the Indians and French . - Johnson, Mrs. (Susannah Willard), 1730-1810.; Carlisle, David, 1771-1835 printer. (Walpole, Newhampshire, Printed by D. Carlisle, jun., 1796)
WHS copy imperfect: half of p. 9-10 is torn away. Mrs. Johnson and her companions were taken prisoners at "No. 4," now Charlestown, N. H., in a raid of Indians from St. Francis, Canada, in Aug. 1754. "Part of the following pages were dictated by Mrs. Johnson, now Mrs. Hastings, herself, and part were taken from minutes made by Mr. Johnson and herself, during their imprisonment."--p. 2. Sabin Mode of access: Internet. WHS copy acquired 2/17/16; inv. 785.